Promise and challenges facing public administration - Posner, Paul L. (2009)
Many nations are on the brink of facing extraordinary and unprecedented challenges in public management. A more competitive global economy is creating more fiscal and economic pressures on government budgets at the same time that expectations have risen for effective government interventions in an ever wider range of problems, including saving markets from themselves. Public administrators face daunting challenges in dealing with ever more complex problems with limits on staff and authority stemming from a declining trust in government among the public. Promoting successful government roles in an era of widespread public ambivalence about government is the central challenged faced by the Obama administration in the United States, an administration committed to expanding the role of government in dealing with major problems such as health care and financial market regulation. Governments throughout the world can learn some lessons from the successes and failures experienced in the United States as they come to grips with the often conflicting pressures stemming from global markets and domestic political forces.
Keywords: Public administration; Transparency in government; Public administration -- Educational aspects; Political institutions and public administration; Eastern Regional Organization for Public Administration (EROPA)